2018
DOI: 10.1128/iai.00899-17
|View full text |Cite
|
Sign up to set email alerts
|

TCRβ Combinatorial Immunoreceptor Expression by Neutrophils Correlates with Parasite Burden and Enhanced Phagocytosis during a Plasmodium berghei ANKA Malaria Infection

Abstract: Recent studies have demonstrated that a subpopulation of neutrophils express the TCRαβ combinatorial immunoreceptor in humans and mice. Here, we report that a ANKA murine malaria infection induces expansion of TCRβ expressing CD11b Ly6G neutrophils in the spleen during the early phase of infection. Measurement of TCRβ transcript and protein levels of neutrophils in wild-type versus nude and knockout mice establishes that the observed expression is not a consequence of nonspecific antibody staining or passive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, recent studies provide conclusive evidence that small subpopulations of monocytes, the second major phagocyte population in the circulation next to neutrophils, also constitutively express TCRαβ variable immune receptors [8] , [9] . Importantly, both the TCRαβ in neutrophils and in macrophages have been implicated by us and others in disease [10] , [11] , [12] , [13] , [14] . Of note, most recent studies from our laboratory and others provide evidence for the expression of the second variable immune receptor based on immunoglobulin heavy and light chain genes by cells of the myeloid lineage [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, recent studies provide conclusive evidence that small subpopulations of monocytes, the second major phagocyte population in the circulation next to neutrophils, also constitutively express TCRαβ variable immune receptors [8] , [9] . Importantly, both the TCRαβ in neutrophils and in macrophages have been implicated by us and others in disease [10] , [11] , [12] , [13] , [14] . Of note, most recent studies from our laboratory and others provide evidence for the expression of the second variable immune receptor based on immunoglobulin heavy and light chain genes by cells of the myeloid lineage [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 83%
“…Ensuing studies showed the recombination of TCR αβ/γδ in monocytes and macrophages [9, 10] as well as TCR γδ in eosinophils [11]. Interestingly, recent studies present the induction of TCRβ expression in neutrophils and macrophages during malaria infection [12, 13]. Furthermore, an implication of these TCR based myeloid variable immune receptors in several chronic diseases like autoimmune disease [14], chronic periodontitis [15], tuberculosis [9] and atherosclerosis [16] was shown.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the authors also revealed that infection of macrophages from healthy individuals with mycobacteria triggered formation of clusters that express restricted TCR Vβ repertoires 48 . Additionally, several studies have also observed the existence of the TCR + macrophages/monocytes and veri ed by different approaches in human peripheral blood, tumor microenvironment, artery, spleen and the bone marrow 49,50,51,52,53,54 . All these studies demonstrated the existence of macrophages/monocytes with TCRαβ or TCRδγ in health and diseased human or murine tissue.…”
Section: Discussionmentioning
confidence: 94%